Initiatives of Urban Agriculture in Semarang City: Pathways for Sustainability - Hasanah, Zahra Nur; Handayani, Wiwandari; Martuti, Nana Kariada Tri (MATEC web of conferences, 2019)
Urban agriculture (UA) has become a popular concept to bridge growth of urban areas with adequate provision of agricultural land, cheap and healthy food. UA in Semarang began to be encouraged by Semarang City Government since 2015 and involves family welfare groups for its implementation. Most of the people involved in UA activities are often based on hobbies whereas some of them start reaching out to businesses. This study aims to elaborate the initiatives from government, community/individual, university, and corporation to promote UA in Semarang. The methods were conducted by using interactive analysis model which is presented by Miles, Huberman, and Saldaña. By elaborate the initiatives of urban agriculture in Semarang, the study shows that initiatives from communities/individual are more promising to promote sustainability rather than initiatives which comes from the government. The major difference among initiatives is due to community eagerness to do UA activities if it comes from their interests and desires, whereas initiatives from the government are more likely to encourage community participation and as part of social innovation.